Code Switching Used in Novel “The Player” By Alia Zalea - Ayudhea Putri, Wayan Denaya; Seri Malini, Ni Luh Nyoman; Suastra, I Made; Saientisna, Made Detriasmita (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
This study aims at identifying the types and functions of code-switching uttered by the characters in the novel “The Player”. The data was taken from the novel “The Player” by an Indonesian female author, Aliazalea published in 2020. This study used a theory proposed by Hoffman (1991) to identify the types of code-switching. Furthermore, the theory proposed by Gumperz (1982) was used to identify the functions applied in the code-switching found in the novel. The content analysis method was used to analyze the data with descriptive presentation. As a result, 35 codes switching were found in the characters in the novel. The types of code-switching proposed by Hoffman (1991) are inter-sentential switching occurred 9 times, intra-sentential switching occurred 15 times, and emblematic switching occurred 11 times. There are 3 functions implied in the code-switching found from 6 functions proposed by Gumperz (1982). They are interjection, message qualification, and personalization. The other 3 functions are quotation, addressee specification, and reiteration which do not appear in the data. From the analysis, it could be concluded that intra-sentential switching is the type of code-switching most frequently used by the characters. Personalization is the function most frequently implied in code-switching as the characters tend to convey their thoughts by switching the language.